Comparative Outcome of Cesarean Hysterectomy Versus Myometrial Resection among Patients of Morbid Adherent Placenta - Shazia Ashraf, Hina Khalil, Afshan Batool, Zain-Ul-Abideen (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Due to various aspects related to the complications observed in the morbid adherent placenta, there are different ways to treat the effective condition including surgical techniques like myometrial resection or also known as local resection or cesarean hysterectomy. Objective: To compare the outcome of cesarean hysterectomy versus myometrial resection among patients of morbid adherent placenta. Study Design: Prospective study. Place and Duration of Study: Department of Obstetrics & Gynaecology, Gujranwala Medical College, Gujranwala from 1st January 2023 to 30th June 2023. Methodology: On hundred cases of pregnant women admitted with ultrasonographic diagnosis of morbid adherent placenta, requiring hysterectomy and age between 18-45 years were included. The patients were divided into two groups. Group 1 was those patients who underwent cesarean hysterectomy while in group 2 underwent myometrial resection as planned. A well-structured proforma was designed for entering data in relation to mode of surgery, the status of booking, hospital stay and complications related within both procedural comparison. The risks and outcomes of both procedures in terms of blood transfusion requirements and other complications were recorded. Results: The mean age of the patients were 31.3±5.1 years with majority having an emergency cesarean hysterectomy/myometerial resection procedure. There were 64% versus 60% such cases which arrived for their hysterectomy of morbid adherent placenta without prior booking. Majority of the patients were multiparous with only 14% patients from myometrium resection being nulliparous. The hospital stay post cesarean was less in myometrium resection than cesarean hysterectomy respectively (5.1±1.3 days vs 6.4±2.5 days). In the present study the bladder injury, blood loss and relaparotomy was only presented in 8%, 18% and 4% cases in myometrium resection in comparison to 24%, 36% and 16% those in cesarean hysterectomy. The post operative infections as well as hematoma formation were also presented only in 20% and 8% patients in Group MR vs 44% and 20% in cesarean hysterectomy respectively. Conclusion: The myometrium resection is a more reliable, effective method in comparison to cesarean hysterectomy with less complications and blood loss, minimal hospital stay, less infection and hematoma risks. Keywords: Outcome, Cesarean hysterectomy, Myometrial resection, Morbid adherent placenta